An Analysis of oral health problems in a sample of asian countries: A case study in the elderly population in an old people’s home in Dhaka City, Bangladesh - Zinat Afsar (2019)
Introduction: The investigation is aimed to assess oral health problems in the elderly population in an old people’s home in Dhaka city, Bangladesh. This is a cross-sectional study which included 22 population selected by random sampling method. Written consent was taken from the participants. A pre-tried close-ended questionnaire was utilized for the study. In 1900, 3.1 million human beings or 4 percent of the populace, were 65 years or more aged; by using 2005, the range had expanded to 34.3 million human beings or 12.4 percent of the population, an expansion of the greater than ten times. To evaluate the specific patient, the dental practitioner needs to comprehend the culture, mental, educational, social, economic, nutritional and chronologically particular encounters that may have influenced his or her life. Materials and Method: Of 25 questionnaires distributed to an Old People’s home, 22 were returned. The respondents were aged between 55 to 77 years old. Women comprised 63.6% of the sample. Results: The result of this study shows that 81.8% had habit of cleaning their teeth while 18.2% were not cleaning teeth. It was seen that 81.80% brushed their teeth using toothbrush and 95.5% using tooth paste. 45% brushed only once a day, 30% brush twice a day while 25% brushed more than twice per day. Of 81.8% who used the brush, 68.4% participants change their brush in every 3-6 months, 26.3% change every 2 months and 5.3% change only every month. Surprisingly, 72.8% of the respondents were aware of using fluoridated toothpaste and only 22.7% were not using it. 100% of the participants reported that they had suffered from dental problems and 50% of the respondents said that they had oral bad odor problems. Tobacco and pan/betel nut chewers 69.2% of respondents, had a greater risk of oral problems. 90.9% of the participants visited a dentist and pain was the main factor for them to visit the dentist chamber or hospital. 72.70% of the participant said that dental treatment cost is very high, and this is one of the major reasons to visit less in dental chambers or hospitals. 81.8% participants feel that dental caries is the most widely recognized dental disease, major factor being irregular brushing followed by consuming more desserts. Conclusion: Consequences of this study demonstrate that almost all participants oral hygiene practice, knowledge level and utilizing tobacco and chewing pan and betel nut propensities in the population of old people’s home in Dhaka city require change.